XIX & XX Century : Paintings, Works on Paper and Sculptures. - Galerie Patrick Derom, Brussels (Brussels : Galerie Patrick Derom, 1988)
Brusselmans, Jean ; Degouve de Nuncques, William ; De Smet, Gustave ; Ensor, James ; Evenepoel, Henri ; Fabry, Emile ; Gailliard, Jean-Jacques ; Guiette, René ; Jefferys, Marcel ; Jespers, Floris ; Khnopff, Fernand ; Lambert-Rucki, Jean ; Langaskens, Maurice ; etc.
XIX & XX Century : Paintings, Works on Paper and Sculptures, Galerie Patrick Derom, Brussels, Autumn 1988
boek